Measuring Job Performance of The Economic Creative Business upon Women Enterpreneurs Base (Case Study at Online Bunda Community Bogor Branch Using Balance Scorecard Approach) - Indar Khaerunnisa (The Accounting Journal of Binaniaga, 2018)
Balance scorecard has a privilege in terms of coverage measurement whichis a fairly comprehensive because while taking into consideration the financialperformance. Balance scorecard also consider the performance of non-financialperformance, namely customer, internal business processes, and learning and growth.Referring to the problems encountered by Member of Bunda Online Community, thisresearch examines: "Analysis of Company's Performance by Using BalancedScorecard Approach (A Case Study Economic Creative Entrepreneur at Bunda OnlineCommunity)." Because until now Bunda Online Community has not been using thebalanced scorecard to measure its job performance. The population of this study arepermanent employees and 100 samples are taken as respondents. As for thecustomer respondents specified by 52 respondents total reseller and costumer inBogor is only 52 reseller and costumer, however, it has obtained only 30 respondentswho participated. Data used in this study are primary and secondary data. Based onthe research and analysis, it can be concluded several things as the following: 1) Theperformance of the financial perspective on Economic Creative Entrepreneur in BundaOnline Community as a whole can be inferred or quite enough, in general financialratios increased except ROA and TATO. 2) The performance of the customerperspective on Economic Creative Entrepreneur in Bunda Online Community as awhole can be inferred bad, because of poor customer satisfaction in the company'sability to maintain customer retention is also bad while in the company's ability to docustomer acquisition is medium. 3) The performance of internal business processperspective on Economic Creative Entrepreneur in Bunda Online Community isenough, because innovation occurs only once during the past two years and there isnot declining operating activities due to consistent time on the production clothingprocess. 4) The performance of learning and growth perspective in the EconomicCreative Entrepreneur in Bunda Online Community may be concluded either onaspects of employee turnover or both criteria which decreasing employee productivity.Level of employee satisfaction is concluded less satisfied.